Developing a logotherapeutic model for understanding victims of sexual assault (2015)
Presently, there is no available logotherapeutic model for understanding the experiences of persons in crises, specifically the victims of sexual assault in Nigeria. The paper first reviewed the literature on some of the available models: equilibrium, cognitive and psychosocial transition. The author has added the existential/logotherapeutic model to literature and based on this model subsequently developed a technique in order to better identify the condition of victims of sexual assault to quickly pave the way for suitable therapy. The paper concluded that when compared with other models, the logotherapeutic model is effective for better understanding and as an intervention strategy in practice for logotherapists and non-logotherapists.